تحليل أداء بارامترات الوصلة الميكروية باستخدام المنطق العائم - جورج, كابي (Latakia University Journal -Engineering Sciences Series, 2016)
This work aims to analyze the performance of the microwave radio link’s parameters used to connect different systems and intra systems. Fuzzy logic technique is used to study the difficulties of the radio link’s parameters based on type of modulation, and distance between the receiver and transmitter. Four parameters are used as an input parameters for the fuzzy logic system mainly: required power, the length of the microwave radio link, modulation type and the signal to noise ratio(S/N). The output parameter is determined to be the microwave link capacity. Analytical study to select the optimal microwave radio link parameters to examine the efficiency of the radio link capacity will be shown. Additionally, studying the input and output memberships of the microwave radio link parameters using fuzzy logic will be explained.يهدف البحث إلى تحليل أداء بارامترات الوصلة الميكروية المستخدمة في أنظمة الربط بين مكونات نظام الاتصال الواحد وبين أنظمة الاتصال المختلفة فيما بينها. استخدمت في الدراسة تقنية المنطق العائم لتحليل مشاكل الأداء للوصلة الميكروية اعتماداً على كل من نوع التعديل المستخدم والمسافة بين المرسل والمستقبل. حيث تم معالجة أربعة بارامترات لمتحولات الدخل في نظام المنطق العائم وهي : الاستطاعة اللازمة و طول الوصلة الميكروية ونمط التعديل المستخدم و نسبة الإشارة إلى الضجيج ، بينما اعتمد بارامتر واحد للخرج وهو سعة الوصلة الميكروية Microwave Link capacity.كما تم تقديم دراسة تحليلية لتحديد القيم المثلى لبارامترات الأداء الرئيسية المعتمدة لتحديد فعالية الوصلة بالإضافة إلى دراسة توابع العضوية لكل من محددات الدخل والخرج باستخدام تقنية المنطق العائم.